If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7-3=8-8(x+2)+2x
We move all terms to the left:
7-3-(8-8(x+2)+2x)=0
We add all the numbers together, and all the variables
-(8-8(x+2)+2x)+4=0
We calculate terms in parentheses: -(8-8(x+2)+2x), so:We get rid of parentheses
8-8(x+2)+2x
determiningTheFunctionDomain -8(x+2)+2x+8
We add all the numbers together, and all the variables
2x-8(x+2)+8
We multiply parentheses
2x-8x-16+8
We add all the numbers together, and all the variables
-6x-8
Back to the equation:
-(-6x-8)
6x+8+4=0
We add all the numbers together, and all the variables
6x+12=0
We move all terms containing x to the left, all other terms to the right
6x=-12
x=-12/6
x=-2
| 3/4x+8/1=41 | | 9+6(x+4)=8-5 | | 3x-9x+7=-9-(-4) | | 28=u+10(5) | | 0.8x=1.75 | | 9x-8x+7=-8 | | 3/4(x+9)=15 | | 8=−18+3/8(16−40n) | | -58=2(2+n)-3(-6n-6) | | -8(7n+7)=-224 | | 92=-4(2r—5) | | 2(7+7x)=-98 | | -26d=364 | | 3(x-1)=6(1/2+8) | | 10x-6x-x=15 | | 19-7n=7(-3n-3)-2 | | 1/2r+-3/2=2r+-12 | | 15=60-1.5x | | -10=x/4-8 | | 91=7(5+b) | | 4/5(x)=7/4 | | -6=9x-8x+3 | | 6.5=n+9 | | -75=3(6x+5) | | 3/5+3/2x-1=0 | | 74=2(3x+7) | | 48=4(9x+3) | | 6x+3-7=6x-4 | | 3x/2+1/2=2x/3-2/3 | | -12-m=36-9m | | 13x-17=61 | | x^-5x-24x=0 |